Impact of sleep bruxism on training-induced cortical plasticity. Issue 3 (July 2019) - Ikuta, Mai; Iida, Takashi; Kothari, Mohit; Shimada, Akiko; Komiyama, Osamu; Svensson, Peter
Abstract: Purpose: To investigate if sleep bruxism (SB) influences training-induced cortical plasticity and performance in terms of accuracy and precision of a tooth-clenching task (TCT). Methods: Thirty-eight participants were allocated into SB group (N = 19) and control group (N = 19) according to presence of SB based on a 2-week screening. The participants were instructed to perform a standardized TCT for 58 min at three different force levels (10%, 20% and 40% of maximum voluntary contraction; MVC) in three series (first and third without visual-feedback and second with visual-feedback). Accuracy and precision of the TCT were calculated from actual bite force values. Transcranial magnetic stimulation was applied to elicit motor evoked potentials (MEPs) from the masseter and first dorsal interosseous muscle (FDI) before the TCT (pre-TCT-session) and 5-min after the TCT (post-TCT-session). Results: Accuracy was significantly dependent on the series and target force level (P < 0.001), however, there was a significant decrease only in the control group at 10% MVC from first to third session (P < 0.001). No significant differences between groups were observed for the precision of the TCT. Masseter MEPs in the SB group in the pre-TCT-session at 120% and 160% motor threshold were significantly lower than in the control group (P < 0.05). Masseter MEPs of the control group in the post-TCT-session were significantly higher than the pre-TCT-session (P < 0.05) but not SB. FDI MEPs were only dependent on stimulus intensity (P < 0.001). Conclusions: SB is associated with significant changes not only in excitability of corticomotor control but also motor learning of jaw movements and force control.